On ludic photography. (2nd September 2021) - Buse, Peter
Abstract : This article explores "the play element in photography", to adapt a key phrase from Johan Huizinga's Homo Ludens (1938). The context for this exploration is the melancholic paradigm that dominates much of contemporary writing and thinking about vernacular or popular photography, a paradigm that emphasises memory, death and mourning, at the expense of other practices and dispositions, not least the ludic. It notes that the existing literature on photography and play concentrates almost entirely on humorous images: optical jokes, trick photography, and a wide variety of distorted pictures. But play is an activity, a practice, as much as it is a product or an outcome. In other words, the ludic in photography is not just a quality of the object photographed, but of a photographic doing . Following this principle, the article shows the ways in which key modes of play such as competition, chance, make-believe and vertigo, are at work in photographic practices old and new, including in the aerostatic photography of Félix Nadar, with which it begins and ends.